2017
DOI: 10.1007/s40263-017-0460-x
|View full text |Cite
|
Sign up to set email alerts
|

Idarucizumab in Dabigatran-Treated Patients with Acute Ischemic Stroke Receiving Alteplase: A Systematic Review of the Available Evidence

Abstract: Background and PurposeCurrent guidelines do not recommend the use of intravenous recombinant tissue plasminogen activator in patients with acute ischemic stroke who receive direct oral anticoagulants. While the humanized monoclonal antibody idarucizumab can quickly reverse the anticoagulant effects of the thrombin inhibitor dabigatran, safety data for subsequent tissue plasminogen activator treatment are sparse. Here, we review current knowledge about dabigatran reversal prior to systemic reperfusion treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 42 publications
(36 reference statements)
3
23
0
5
Order By: Relevance
“…In this interim analysis, nine patients were treated with idarucizumab before treatment of ischemic stroke (thrombolysis, thrombectomy, or bypass for ischemic stroke). Several case reports suggest that thrombolysis and thrombectomy can be performed safely after dabigatran reversal with idarucizumab [22,23]. Although these data are limited, recommendations have been published regarding acute reperfusion therapy with idarucizumab for patients with ischemic stroke receiving dabigatran [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In this interim analysis, nine patients were treated with idarucizumab before treatment of ischemic stroke (thrombolysis, thrombectomy, or bypass for ischemic stroke). Several case reports suggest that thrombolysis and thrombectomy can be performed safely after dabigatran reversal with idarucizumab [22,23]. Although these data are limited, recommendations have been published regarding acute reperfusion therapy with idarucizumab for patients with ischemic stroke receiving dabigatran [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in this systematic review, stroke severity increased, with moderate to severe stroke in 63% of cases (vs 10%4), and median time to IVT increasing to 173 min (vs 155 min4). Despite increasing stroke severity and time to IVT, the rate of favourable outcomes is higher than previously reported (81.9% vs 72%), suggesting that the treatment paradigm might be considered also for all patients with acute ischaemic stroke, including those with moderate to severe stroke and longer time windows for IVT.…”
Section: Resultsmentioning
confidence: 66%
“…Compared with the existing systematic review,4 we have been able to double included papers (24 vs 13) and enlarge the cohort of more than a third (55 patients vs 40). Moreover, in this systematic review, stroke severity increased, with moderate to severe stroke in 63% of cases (vs 10%4), and median time to IVT increasing to 173 min (vs 155 min4).…”
Section: Resultsmentioning
confidence: 99%
“…Previously published cases usually had good outcomes as well, but were generally of lower initial severity . A systematic review of 21 patients with a median baseline NIHSS of 10 by Pikija et al identified 16% of unfavorable outcome (increase in NIHSS, recurrent stroke, symptomatic post‐thrombolysis intracranial hemorrhage, or death). No systemic bleeding, venous thrombosis, or allergic reactions were reported.…”
Section: Discussionmentioning
confidence: 99%